Diversification of habenular organization and asymmetries in teleosts: Insights from the Atlantic salmon and European eel - Michel, Léo; Palma, Karina; Cerda, Mauricio; Lagadec, Ronan; Mayeur, Hélène; Fuentès, Michaël; Besseau, Laurence; Martin, Patrick; Magnanou, Elodie; Blader, Patrick; Concha, Miguel L.; Mazan, Sylvie (Frontiers in Cell and Developmental Biology, 2022)
Habenulae asymmetries are widespread across vertebrates and analyses in zebrafish, the reference model organism for this process, have provided insight into their molecular nature, their mechanisms of formation and their important roles in the integration of environmental and internal cues with a variety of organismal adaptive responses. However, the generality of the characteristics identified in this species remains an open question, even on a relatively short evolutionary scale, in teleosts. To address this question, we have characterized the broad organization of habenulae in the Atlantic salmon and quantified the asymmetries in each of the identified subdomains. Our results show that a highly conserved partitioning into a dorsal and a ventral component is retained in the Atlantic salmon and that asymmetries are mainly observed in the former as in zebrafish. A remarkable difference is that a prominent left-restricted pax6 positive nucleus is observed in the Atlantic salmon, but undetectable in zebrafish. This nucleus is not observed outside teleosts, and harbors a complex presence/absence pattern in this group, retaining its location and cytoarchitectonic organization in an elopomorph, the European eel. These findings suggest an ancient origin and high evolvability of this trait in the taxon. Taken together, our data raise novel questions about the variability of asymmetries across teleosts and their biological significance depending on ecological contexts.